A paper-supported graphene–ionic liquid array for e-nose application. Issue 14 (21st January 2016) - Zhu, X.; Liu, D.; Chen, Q.; Lin, L.; Jiang, S.; Zhou, H.; Zhao, J.; Wu, J.
Abstract : A graphene e-nose can be simply fabricated by modifying paper-supported rGO (PS-rGO) with a panel of ionic liquids (ILs). Abstract : A flexible graphene sensor array has been fabricated by in situ reduction of a graphene oxide (GO) array patterned on a paper chip. To achieve cross-reactive sensing and gas discrimination ability, the surface of each reduced GO (rGO) spot was modified with different types of ionic liquids (ILs), which could significantly alter the semiconductor properties and consequently the gas sensing behaviour of the paper-supported rGO sensor.